A novel 3D X‐ray computed tomography (CT) method for spatio‐temporal evaluation of waterlogging‐induced aerenchyma formation in barley. Issue 1 (9th April 2022) - Kehoe, Stephen; Byrne, Tomás; Spink, John; Barth, Susanne; Ng, Carl K. Y.; Tracy, Saoirse
Abstract: Increased precipitation during winter months in Western Europe is predicted from climate change. This is expected to increase the frequency of flooding events, with waterlogged conditions becoming more prevalent. A consequence of waterlogging is hypoxic conditions and dying back of roots, thereby negatively affecting plant nutrient uptake, growth, and development. Barley ( Hordeum vulgare L.) forms lysigenous aerenchyma, which are air‐filled pockets within the root to facilitate O2 transport and support root respiration. Current methods for visualizing aerenchyma formation in roots are largely 2D and involve embedding a fixed root segment in resin, followed by destructive sectioning for microscopy. Here, we report the development of an X‐ray computed tomography (CT) acquisition and analytical method for spatio‐temporal identification and quantitation of aerenchyma in 2D and 3D in barley roots without the requirement for chemical fixation, resin embedding, followed by physical sectioning of the root. We demonstrated that the method we have developed can facilitate the identification and quantitation of aerenchyma in barley as early as 9 d post‐waterlogging. The method we have developed can be potentially applied to different plant species and has the potential to support the selection of breeding markers through X‐ray CT phenotyping of aerenchyma. Core Ideas: A new method to view and quantify aerenchyma in barley using X‐ray CT was developed. Aerenchyma are viewed and quantified in both 2D and 3D images. Aerenchyma have been identified as early as 9 d post‐waterlogging.